Perception and Attitude of Civic Education Teachers on Civic Competence of Senior Secondary School Students in Osun State Nigeria - Adeyemi, B. A. (American Journal of Creative Education, 2019)
The study examined the perception of Civic Education teachers on Civic competence of senior secondary school students. It also examined teachers’ perception towards Civic competence of senior secondary school students. It further determined the difference in teachers’ perception and attitude on civic competence of senior secondary school students based on gender. The study adopted survey research design. Teachers of Civic Education in senior secondary schools in Osun State constituted the population for the study. Three hundred (300) teachers constituted the sample size for the study using multi-stage sampling procedure and simple random sampling techniques. An instrument titled: ‘Perception and Attitude of Teachers on Civic Competence Questionnaire’ (PATCCQ) was used for data collection. Two research questions and two hypotheses emanated from the study. Data collected were analyzed using frequency counts, simple percentages and Multivariate Analysis of Variance (MANOVA). The results among others showed that majority of the teachers (67.0%) had positive attitude towards civic competence of their students. Also, there was a significant difference in teachers’ perception on civic competence of senior secondary school students based on gender (F = 8.725, p<0.05) and religion (F = 2.739, p<0.05) respectively. The study concluded that teachers have good perception and positive attitude towards civic competence of senior secondary school students in the study area in Osun State.